Forensic imaging: a new subspeciality of radiology - Dédouit, Fabrice; Grabherr, Silke; Heinze, Sarah; Scheurer, Eva; Yen, Kathrin (Forensic imaging, 2022)
Forensic imaging is often represented as a new field emerging from multidisciplinary work and research in forensic medicine and radiology. However, looking back on the interaction between radiology and forensic medicine, it has to be stated that radiology has always been used also for forensic purposes. This collaboration is therefore nearly as old as radiology itself. The year 1895 is important for radiologists because it was the year of the realization of the first radiography by Wilhelm Conrad Röntgen (Brogdon 1964). In fact, the benefit of radiographs to reveal the body’s hidden secrets started to be practically used in 1895 in the United States of America, and then in 1896 in England (Brogdon 1998). These first forensic radiographs were used for clinical and postmortem purposes. Very early, the possibility of localizing gunshot projectiles on X-ray images was highlighted. These are important facts, because they perfectly illustrate the early interaction between two different medical specialities: Radiology and Forensic Pathology. Interestingly, things are not so different today: Radiology assists clinical forensic medicine as well as forensic pathology. However, one major difference compared to those early experiences is of course that the radiological tools available today have advanced greatly. Those tools permit to document the inside of a human body and to digitalize it in a highly detailed matter. In postmortem cases, the investigation of those digitalized bodies is often called “virtual autopsy” (Thali et al. 2003) and used as complementary tool to conventional forensic autopsy.